Po Mannie i Viscontim. Śmierć w Wenecji we współczesnej literaturze polskiej, rosyjskiej i ukraińskiej - Siemońska, Olga (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article analyzes three pieces of Russian, Ukrainian and Polish contemporary literature on the subject of “the death in Venice”. The authors of the works, by referring to the literary tradition, consciously strengthen the myth of the "the city of death". In their interpretations this myth has two dimensions: the general and the individual. In the general dimension the vision of a dying beauty and fading power encourages reflection on the transitory nature of civilization. The individual dimension is based on the sense of identification of a dying character with a "dying" city, i.e. Venice.